2006
DOI: 10.1007/s00586-006-0151-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of developing new symptomatic vertebral compression fractures after percutaneous vertebroplasty in osteoporotic patients

Abstract: Percutaneous vertebroplasty (PVP) is an efficient procedure to treat pain due to osteoporotic vertebral compression fractures (OVCFs). However, some patient populations experience recurrent vertebral fracture after initial successful procedure. There are a lot of literatures about the effectiveness of this procedure but few concerning the development of recurrent, new compression fracture. This is a retrospective review of all PVPs performed in author's institution from September 1999 to December 2001 to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 27 publications
0
53
3
2
Order By: Relevance
“…This is still only a theory, however, and it is not clear whether there truly is an increased risk associated with vertebroplasty. Our results did not show an increased refracture rate, compared with reports of the natural course, which suggest that NVCFs that develop after vertebroplastic intervention might be the result of the osteoporosis itself, and not due to the intervention, as previous reports have pointed [11,21,25]. As for the risk of subsequent fracture after vertebroplasty, various causative factors have been proposed [7, 11, 13-15, 20, 21, 24].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…This is still only a theory, however, and it is not clear whether there truly is an increased risk associated with vertebroplasty. Our results did not show an increased refracture rate, compared with reports of the natural course, which suggest that NVCFs that develop after vertebroplastic intervention might be the result of the osteoporosis itself, and not due to the intervention, as previous reports have pointed [11,21,25]. As for the risk of subsequent fracture after vertebroplasty, various causative factors have been proposed [7, 11, 13-15, 20, 21, 24].…”
Section: Discussioncontrasting
confidence: 72%
“…Lindsay [12] reported the incidence of a NVCF in the subsequent year following an osteoporotic fracture to be 19.2%. Various studies have reported the 1-year NVCF rate after PVP or PKP to be 20.5% (Lin et al [14]), 21.7% (Syed et al [21], symptomatic), 7.8% (Lee et al [11], symptomatic), 7.9% (Kim et al [7]), and 15.5% (Moon et al [15]). In our study, which is larger in case population, the NVCF-free rate of 85.0% over 1 year is comparable to these data; however, our study was confined to only symptomatic subsequent NVCFs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous risk factors have been reported for the occurrence of new adjacent VCFs after PVP, including growing age, previous vertebral fractures [16], steroids [30], vertebroplasty at the TL junction [15], low bone mineral density, proximity to the initial fracture site cement leakage into the discs [12] and vacuum clefts within the compression fracture [31].…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Lee et al [17] investigates the factors related to the development of new symptomatic vertebral compression fractures after percutaneous vertebroplasty in osteoporotic patients. A retrospective review of 244 cases of PVP was performed.…”
Section: Vertebroplastymentioning
confidence: 99%